Analisis Kandungan Mineral Pada Tepung Campuran Pisang Awak Dan Tepung Beras Serta Sumbangan Mineralnya Terhadap Angka Kecukupan Gizi Bayi - Masria Sitompul; Jumirah .; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Complementary Feeding is given to infant while it is 6 months old to fulfill as nutrition, especially micro nutrient like minerals. Nowadays, mineral content of local complementary feeding have not know yet, and one of local complementary feeding that is treated became banana  flour with additional rice flour as a base for complementary feeding. This research aims to know the mineral content of mixed awak banana and rice flour and its contribution to infant Recommended Dietary Allowance (RDA). This research is descriptive study conducted in the laboratory which based on chemical analytic to mineral content in mixed of awak banana and rice flour. Analyzed the content of iron and zinc by Atomic Absorption Spectrophotometry method (AAS), the content of potassium, natrium, and selenium by Inductively Couple Plasma method (ICP), the content of phosphor by spectrophotometry method, the content of calcium by titration method and iodide content by HPLC method performed in the laboratory of PT. Sarawanti Indo Genetech Bogor. The results of the research suggested that mixed of awak banana and rice flour contain macro mineral by calcium, potassium, natrium and phosphor for 14,70 mg, 396,40 mg, 8,58 mg and 100,7 mg respectively. Whereas the content of micro mineral in mixed of awak banana flour and rice flour contain the iron, zinc, iodide and selenium for 3,43 mg, 8,08 mg, 42,74 ug and 0,30 ug respectively. Both macro mineral and micro mineral, except zinc and potassium in mixed of awak banana and rice flour has not fulfill the standart of complementary feeding appropriate 224/Menkes/SK/II/2007 aged 7-12 months according the Widyakarya Nasional Pangan dan Gizi 2004. Keywords : mineral content, awak banana, rice flour, recommended dietary allowance.